Экономические проблемы Индии - Вадиа П. А. (Издательство иностранной литературы, 1957)
Экземпляры: КХ (20130206) / Инвентарный номер: 211098 / Цена: 35.70 / Сис.шифр: 33Б / Авт.знак: В 12 / ГРНТИ: 06.91 / ББК: 65